Balancing of Load in Smart Grid Environment Using Cloud Computing - Saravanan, D.; Vallabhaneni, S. Parvathi; Akram, Faiz; Selvam, P. M. Sithar; Priya, T.; Maurya, Sudhanshu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Based on the time-of-use patterns of individual customer electricity consumption, this article proposes a method for regulating the load on a single feeder and a node or distribution transformer. The reality that different customers use different amounts of electricity at different times is accounted for by this method. The findings of a research project that made use of three different service agent strategies in addition to an algorithm for live VM migration are described in this article. The authors of this paper were responsible for carrying out the investigation. The GWO algorithm was put into place as a means of finding a middle ground between the variety of different network resources that were available at one time. Using VM Migration as an experimental setup, we present the findings of the GWO algorithm in this article. VMware is responsible for developing VM Migration. Cloud service providers have the possibility to implement the GWO energy efficiency enhancement system, which can save them both money and effort. This is a win-win situation for everyone involved.